Pengembangan Model Pelatihan Berkelanjutan Berbasis Lesson Study untuk Meningkatkan Kompetisi Pengawas Sekolah/Madrasah - Andi Nurochmah; Andi Mappincara (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This research is a Research and development (R&D) located in Wattan Soppeng Regency. The background of this research is the importance of continuous training to improve the competence of professional school/madrasah supervisors in Wattan Soppeng Regency. The main problem in this research and development is how to develop an effective training model, valid, practical, useful for improving the competence of school/madrasah supervisorsThe research objective is to produce and apply an effective lesson study-based training model product to increase the competence of school/madrasah supervisors. The benefit of the research is as a reference to be used as the basis for a continuous training program for school/madrasah supervisors. training model Research using the procedure Borg & Gall (2003) which consists of three stages of development, namely pre-development, development and post-development. conduct product designs on leadership models which are then validated, conduct limited trials and wider tests, and observe model implementation in Wattan Soppeng Regency.The research objective is to produce and apply an effective lesson study-based training model product to increase the competence of school/madrasah supervisors. The benefit of the research is as a reference to be used as the basis for a continuous training program for school/madrasah supervisors. training model Research using the procedure Borg & Gall (2003) which consists of three stages of development, namely pre-development, development and post-development. conduct product designs on leadership models which are then validated, conduct limited trials and wider tests, and observe model implementation in Wattansoppeng RegencyThe data were analyzed by qualitative descriptive, quantitative techniques and inferential analysis tests to see the significance of the effectiveness of the model, the target was school/madrasah supervisors consisting of 30 school/madrasah supervisors. The results of the implementation of the model, it can be concluded that the implementation of MPB2LSKP-SM has proven to be able to improve the ability of school/madrasah supervisors, therefore MPB2LSKP-SM is effective to be used in an effort to increase the competence of school/madrasah supervisors or the MPB2LSKP-SM model shows significant effectiveness. Keywords: Continuing Training Model, Lesson Study, Competence Improvement of School/Madrasah Supervisors